2017
DOI: 10.17776/cumuscij.291995
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Measurements of Calcaneus;Boehler’sangle and bone length estimation

Abstract: Measurements of bones give us information about the individual and the population it belongs to. In these studies, in addition to head and pelvis skeleton, calcaneus bone is also one of the other studied body bones as it can be preserved well. In the present study, 65 (35 right-30 left) well-preserved calcaneus bones were evaluated in Anatomy Laboratories of Cumhuriyet University and Mugla Sıtkı Kocman University. With these bones, 10 linear measurements were made and Boehler's angle was measured. In calcaneus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…In present study Bohler's angle (Table 1) was found to be in between 15-34° which was in accordance with the study done in Caucasia region [16] where they reported the Bohler's angle to be 25-40° and between 28-38° in Nigeria [17] and between 20-40° in Uganda [18]. It was Correlation of MXL of calcaneum with other parameters was done which came out to be significant except for CFH (right side) and DAFW (right side) which was different from the study done in turkey [19] where they found the correlation of MXL with all the parameters except for the BA and WSC (Table 2). The standardized measurements from bones enable us to obtain information such as population affinity, gender, age, history of the individual before death and time of death [20].…”
Section: Discussionsupporting
confidence: 72%
“…In present study Bohler's angle (Table 1) was found to be in between 15-34° which was in accordance with the study done in Caucasia region [16] where they reported the Bohler's angle to be 25-40° and between 28-38° in Nigeria [17] and between 20-40° in Uganda [18]. It was Correlation of MXL of calcaneum with other parameters was done which came out to be significant except for CFH (right side) and DAFW (right side) which was different from the study done in turkey [19] where they found the correlation of MXL with all the parameters except for the BA and WSC (Table 2). The standardized measurements from bones enable us to obtain information such as population affinity, gender, age, history of the individual before death and time of death [20].…”
Section: Discussionsupporting
confidence: 72%
“…Calcaneus ve diğer tarsal kemiklerle beraber ayağın anatomik bilgisi ergonomik olarak ayağa uygun ayakkabı tasarımı için de gereklidir (2)(3)(4)(5). Kemikler üzerinde yapılan morfometrik ölçümler, kemiğe ait olan bireyin yaş, cinsiyet, boy, ırk, ölümden önceki geçmişi ve ölüm zamanı ile ilgili bilgiler verebilmektedir (6). Adli tıp, antropoloji ve biyoarkeoloji alanlarında farklı ölçümler ve farklı referans popülasyonları ile kemikler üzerinde çok fazla çalışma yapılmıştır (1,(6)(7)(8)(9)(10)(11)(12)(13).…”
Section: Introductionunclassified
“…Kemikler üzerinde yapılan morfometrik ölçümler, kemiğe ait olan bireyin yaş, cinsiyet, boy, ırk, ölümden önceki geçmişi ve ölüm zamanı ile ilgili bilgiler verebilmektedir (6). Adli tıp, antropoloji ve biyoarkeoloji alanlarında farklı ölçümler ve farklı referans popülasyonları ile kemikler üzerinde çok fazla çalışma yapılmıştır (1,(6)(7)(8)(9)(10)(11)(12)(13). Cranium ve pelvis iskeleti kemikleri antropoloji için sıklıkla kullanılan kemiklerdendir (6).…”
Section: Introductionunclassified
See 2 more Smart Citations